PENGEMBANGAN E-MODUL AKTIVITAS FISIK UNTUK PENCEGAHAN DIABETES MELITUS REMAJA BAGI GURU DI SMPN 18 BANDUNG - Larasati Eka Putri; Ridwan Setiawan (Jurnal Kesehatan Siliwangi, 2025)
The prevalence of juvenile diabetes mellitus (DM) in Bandung increased sharply from 9 cases in 2021 to 53 cases in 2022. Contributing factors include low health education awareness and the inactivity of 65% of adolescents. To address this, an e-module was developed for teachers at SMPN 18 Bandung, a school with students at high risk of DM due to hereditary factors and obesity. This study aimed to develop a physical activity e-module for teachers at SMP Negeri 18 Bandung to prevent adolescent DM, utilizing the ADDIE model. This research employed a Research and Development (R&D) methodology utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study involved a sample of 31 homeroom teachers from SMPN 18 Bandung City, with collected data being analyzed using both qualitative and quantitative methods. The ADDIE-based e-module was rated "highly feasible" by material (93.3%) and media (89.5%) experts. A Wilcoxon test (p=0.000) indicated a significant improvement in teachers' knowledge, with mean scores rising from 47 (pre-test) to 89 (post-test). Additionally, 96.8% of participants achieved the "good" knowledge category. Positive engagement on Instagram (1,041 views, 69 likes) further demonstrated the media's effectiveness. The physical activity e-module for DM prevention, developed using the ADDIE model, proved both valid (rated "highly feasible" by experts) and effective in enhancing teachers' knowledge. As an interactive educational tool, it successfully raises awareness about DM and its prevention, receiving positive user feedback. Implementing this e-module in schools is recommended as an effective health education medium.